Feasibility of Transformable Party Dress Inspired by Deep Sea Waves in Design and Aesthetics - Dian Putri Wijaya; Wulansari Prasetyaningtyas (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
This study aims to test the feasibility of deep-sea wave origin party clothing with the concept of transformation in terms of design and aesthetics. The method used in this study uses a quantitative descriptive approach with data collection techniques using observation sheets that are shared with expert panelists and trained panelists. The research instrument in the validity test used the Aiken's Coefficient V with the validity results of 14 assessment items having a V value of > 0.75 so that all items were declared valid. The reliability test used the Intraclass Correlation Coefficient (ICC) with an average measurement value  of 0.954, showing very good reliability. Data analysis in this study used descriptive statistical analysis. The results of the study show that the party clothing that is the source of the idea of deep sea waves with the concept of transformation is stated to be very feasible in terms of design and aesthetics. The results of the feasibility test conducted on the two design and aesthetic indicators were included in the very feasible category with an overall average percentage of 92.08% with the highest assessment results being aesthetic indicators with a percentage of 46.14% and the lowest assessment being design indicators with a percentage of 45.94%.